Synthesis, characterization and biological activity of Copper (II) and Zinc (II) complexes of Thiosemicarbazones and their N(4)-substituted derivatives derived from 2,4-Dihydroxybenzaldehyde / Tan Kong Wai - Tan, Kong Wai (2010)
Four thiosemicarbazones ligands (1-4) have been prepared with good yield by refluxing 2,4-dihydroxybenzaldehyde with thiosemicarbazide or N(4)-substituted thiosemicarbazide in ethanol or methanol. From these four ligands, 16 new ternary metal complexes (5-20) with the general formulation of M(B)L have been prepared from the reactions of metal acetates with 2,4-dihydroxybenzaldehyde N(4)-substituted thiosemicarbazone in the presence of N,N-heterocyclic base (M2+ = Zn2+ or Cu2+; B = 2,2'-bipyridine, (bpy); 1,10-phenanthroline, (phen); L2- = doubly deprotonated thiosemicarbazones = 2,4-dihydroxybenzaldehyde thiosemicarbazonato, (HT); 2,4-dihydroxybenzaldehyde 4-methylthiosemicarbazonato, (HM); 2,4-dihydroxybenzaldehyde 4-ethylthiosemicarbazonato, (HE) and 2,4-dihydroxybenzaldehyde 4-phenylthiosemicarbazonato, (HP)) These compounds have been characterized by elemental analyses, IR, UV-Vis, NMR and magnetic susceptibility. The structures for ligands (2, 3, 5) and complexes (8, 9, 11, 13 and 18) have been solved by single crystal X-ray crystallography. Results from spectroscopic data and crystal structure analysis show that all the free ligands exist in the thione form. The complexes are mononuclear and five coordinated with the doubly deprotonated thiosemicarbazone as a tridentate ligand coordinating through the phenolic oxygen, azomethine nitrogen and thiolate sulfur while 2,2'-bipyridine or 1,10-phenanthroline as the N,N’-bidentate ligand. The coordination geometries vary from distorted square pyramidal to distorted trigonal bipyramidal. The effect of varying the N(4) substituent from methyl, ethyl to phenyl, metal ions and polpyridyl ligand towards the chemical and biological properties of these compounds (DNA duplex and G-quadruplex binding, nucleolytic, topoisomerase I inhibition and antimicrobial) have been studied. Results from our biological studies show that compounds with more hydrophobic ligands generally have better biological properties. The nucleolytic efficiency of the copper(II) complexes are better than their zinc analogs. Interestingly, complexes Cu(phen)(HM) 18 and Cu(phen)(HE) 19 can induce oxidative DNA cleavage in the absence of exogenous agent.